Lithium prevents scopolamine-induced memory impairment in zebrafish. (18th January 2018) - Zanandrea, Rodrigo; Abreu, Murilo S.; Piato, Angelo; Barcellos, Leonardo J.G.; Giacomini, Ana C.V.V.
Highlights: Lithium prevents memory impairment induced by scopolamine in zebrafish. Lithium decreases exploration activity in zebrafish. Lithium increases the activity of acetylcholinesterase in zebrafish. Abstract: We examined whether lithium carbonate (Li2 CO3, 100 mg/L) is able to prevent memory impairment induced by scopolamine. Moreover, we evaluated the effects of lithium on anxiety-like behavior and acetylcholinesterase activity in adult zebrafish. We demonstrated that lithium prevents the memory impairment induced by scopolamine, decreases exploration and increases the activity of acetylcholinesterase in zebrafish. Collectively, this contributes to a better understanding of the pharmacology of lithium, its interaction with cholinergic neurotransmission, and its possible application to therapeutic treatments aimed at improving cognition.